Transecumenical Filioque - Popoveniuc, Bogdan 1976- (2019)
The present article proposes a hermeneutical interdisciplinary strategy aiming to transpose a part of the great conceptual achievements in conceiving the tri-unitary schema of the Holy Trinity to the understanding of the triadic nature of human person. At the same time, it claims that the scientific knowledge about the structure, behavior and complexity of human mind might be incorporated in the hermeneutical effort of theological understanding. The consequence of this understanding is mutually beneficial. On the one hand, it proves that the theological insights promise a perspective able to provide the desired comprehensive framework necessary for an all-inclusive theory on personality, able to reunite all the three ontological aspects of human being: biological substance, social structure and cultural nature. On the other hand, it offers a new base for the reconceptualization of some of the millennial theological debates. Last, but not the least, it shows that such interdisciplinary ecumenism could provide a base for spiritual personal development, given that the largely referred opposition between theological and scientific knowledge can be dissolved in a comprehensive theanthropic model.
Keywords: (trans)ecumenism; Filioque; Holy Trinity; Human Person; interdisciplinary hermeneutics